STUDENTS’ PERCEPTIONS OF ENGLISH ONLINE LEARNING - Mainar Fitri; Sensia Miranda Alfasari; Mirawati (State Islamic University of Sultan Syarif Kasim Riau, 2026)
Students have different perceptions of learning English via online. This research aimed to describe how students' perceptions of English online learning. This research used a quantitative approach using quantitative descriptive research design and survey method. The data in this research were obtained from a questionnaire with 30 college students at a state Islamic university in Riau Province, Indonesia as a sample of the research chosen by using simple random sampling technique. Overall, the results of this research indicated that the students’ perception of online English learning is negative with an average score of 28.8% which consist of 5 aspects: accessibility (with the percentage of 22%), independent learning (with the percentage of 21%), equality (with the percentage of 21%), effectiveness learning (with the percentage of19%), and communication (with the percentage of 17%). In conclusion, the students have negative perception of learning English via online class.